1. Find the product :- (x-y) (3x-5y)
Answers
Answered by
4
Answer:
3x – 5y) × (x + y)
= x (3x – 5y) + y (3x – 5y)
= 3x2 – 5xy + 3xy – 5y2
= 3x2 – 2xy – 5y2
Putting x = - 1 and y = - 2, we have
[3 (-1) – 5 (-2)] [(1) + (-2)] = 3 (-1)2 – 2 (-1) (-2) – 5 (-2)2
(-3 + 10) (-1 – 2) = 3 – 4 – 20
- 21 = - 21
Therefore,
L.H.S = R.H.S
Hence, verified
Step-by-step explanation:
please mark me in brain list plz plz plz
Answered by
4
Step-by-step explanation:
(3x – 5y) × (x + y)
= x (3x – 5y) + y (3x – 5y)
= 3x2 – 5xy + 3xy – 5y2
= 3x2 – 2xy – 5y2
Putting x = - 1 and y = - 2, we have
[3 (-1) – 5 (-2)] [(1) + (-2)] = 3 (-1)2 – 2 (-1) (-2) – 5 (-2)2
(-3 + 10) (-1 – 2) = 3 – 4 – 20
- 21 = - 21
Therefore,
L.H.S = R.H.S
Hence, verified
Similar questions